Urethane (METH)acrylate resin mortar composition and cured product thereof
The urethane (meth)acrylate resin mortar composition addresses shrinkage and sagging issues by combining urethane (meth)acrylate resin with a water reducing agent and aggregates, enhancing workability and durability in industrial applications.
Patent Information
- Application Number
- JP2023101563
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2025-01-09
AI Technical Summary
Conventional radically polymerizable resin compositions exhibit significant shrinkage during curing, limiting their application in industrial settings and requiring improvements in workability and sagging resistance.
A urethane (meth)acrylate resin mortar composition incorporating a urethane (meth)acrylate resin, a water reducing agent, and aggregates, along with optional metal-containing compounds and thiol compounds, to achieve both workability and sag resistance.
The composition provides improved workability and sag resistance, enabling effective application in industrial settings with reduced shrinkage and enhanced durability.
Smart Images

Figure 2025001850000001 
Figure 2025001850000002 
Figure 2025001850000003
Abstract
Description
[Technical field]
[0001] The present embodiment relates to a urethane (meth)acrylate resin mortar composition and a cured product thereof. [Background technology]
[0002] When general liquid vinyl monomers are polymerized, a significant amount of shrinkage occurs. This shrinkage causes distortion problems when vinyl monomers are used in industrial products. Therefore, it is industrially very meaningful to create a resin with a small shrinkage rate during polymerization.
[0003] Radically polymerizable resin compositions such as unsaturated polyester resins and vinyl ester resins (epoxy acrylates) also usually shrink during curing. Since "styrene" and "methyl methacrylate" are often used as monomers, which are listed in Table 1 of Non-Patent Document 1, unsaturated polyester resins in general formulations shrink in volume by about 8 to 12%, and vinyl ester resins shrink in volume by about 8 to 10%. This figure is considerably larger than the 3-6% volume shrinkage that is typical for epoxy resins, and has prevented unsaturated polyester resins and vinyl ester resins from being used in industrial applications, or from being used in other industries and applications.
[0004] As a method for solving this problem, Patent Document 1 describes the use of polystyrene beads as a low shrinkage material, which reduces the number of manufacturing steps or shortens the manufacturing time, and enables the production of a low shrinkage unsaturated polyester resin composition having excellent low shrinkage properties, dimensional stability, and surface smoothness.
[0005] Furthermore, Patent Document 2 describes that by blending an AB type block copolymer with an unsaturated polyester resin composition, it is possible to obtain a low-shrinkage unsaturated polyester resin composition that has low shrinkage during curing and can be used to produce a molded product with excellent heat resistance.
[0006] In addition, Patent Document 3 describes that by mixing an AB type block copolymer (vinyl acetate-styrene type) consisting of A and B segments and fine silica particles with an unsaturated polyester resin, it is possible to obtain a low-shrinkage unsaturated polyester resin composition that has a large low-shrinkage effect during molding at room temperature or medium temperature and has high water resistance. Furthermore, Patent Document 4 discloses a radical polymerizable resin composition that can suppress shrinkage while maintaining strength by adding an appropriate amount of an expanding material to the radical polymerizable compound. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 11-315198 [Patent Document 2] Patent No. 2794802 [Patent Document 3] Japanese Patent Application Publication No. 05-222282 [Patent Document 4] International Publication No. 2021 / 132140 [Non-patent literature]
[0008] [Non-Patent Document 1] Endo, Tsuyoshi, Is volume shrinkage during polymerization inevitable?, Polymer, Vol. 27, February issue (1978), pp. 108-111. Summary of the Invention [Problem to be solved by the invention]
[0009] In conventional radical polymerizable resin compositions, in order to create resins with low shrinkage, a single blend of thermoplastic resins such as polystyrene or a block copolymer of two or more types is used. In most cases, these function as "shrinkage prevention materials." Furthermore, these resin compositions are based on the idea of offsetting the thermal expansion of the thermoplastic resin due to heat generation during curing and the curing shrinkage of the unsaturated polyester resin, and their applications have often been limited to applications in which hot molding is performed at medium temperatures or higher, such as sheet molding compounds (SMC) and bulk molding compounds (BMC). Moreover, the radically polymerizable resin composition disclosed in Patent Document 4 has room for further improvement in terms of achieving both workability and sagging resistance.
[0010] The present embodiment has been made in consideration of the above-mentioned conventional situation, and aims to provide a urethane (meth)acrylate resin mortar composition that uses a urethane (meth)acrylate resin and incorporates a water-reducing agent, which has the effect of achieving both workability and sagging resistance. [Means for solving the problem]
[0011] That is, this embodiment is described in the following [1] to [6].
[0012] [1] A urethane (meth)acrylate resin (A), Water reducing agent (B), A urethane (meth)acrylate resin mortar composition comprising: an aggregate (C); [2] The urethane (meth)acrylate resin mortar composition according to [1], wherein the water-reducing agent (B) is at least one type of water-reducing agent selected from the group consisting of naphthalenesulfonate-formaldehyde condensates, melamine-formaldehyde condensates, styrenesulfonic acid copolymers, polycarboxylic acids, ligninsulfonic acid, polystyrenesulfonic acid, naphthalenesulfonic acid, and melaminesulfonic acid water-reducing agents. [3] The urethane (meth)acrylate resin mortar composition according to any one of [1] to [3], further comprising a metal-containing compound (D) and a thiol compound (E). [4] The urethane (meth)acrylate resin mortar composition according to [1] or [2], further comprising a radically polymerizable unsaturated monomer (M). [5] The urethane (meth)acrylate resin mortar composition according to any one of [1] to [4], wherein the water-reducing agent (B) is at least one type of water-reducing agent selected from the group consisting of naphthalenesulfonate-formaldehyde condensates, melamine-formaldehyde condensates, and styrenesulfonic acid copolymers. [6] The urethane (meth)acrylate resin mortar composition according to any one of [1] to
[54] , characterized in that the content of the aggregate (C) is 200 to 800 parts by mass per 100 parts by mass of the urethane (meth)acrylate resin composition (A). [7] The urethane (meth)acrylate resin mortar composition according to any one of [1] to [6], further comprising a radical polymerization initiator (G). [8] The urethane (meth)acrylate resin mortar composition according to any one of [1] to [7], wherein the urethane (meth)acrylate resin (A) has a number average molecular weight of 1,000 to 50,000. [9] A cured product of the urethane (meth)acrylate resin mortar composition according to any one of [1] to [8]. Effect of the Invention
[0013] According to this embodiment, it is possible to provide a urethane (meth)acrylate resin mortar composition that has both excellent workability and sagging resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] This embodiment will be described in detail below.
[0015] (Urethane (meth)acrylate resin mortar composition) The urethane (meth)acrylate resin mortar composition according to one embodiment of the present invention (sometimes referred to as the urethane (meth)acrylate resin mortar composition of the present embodiment, or the resin mortar composition of the present embodiment) contains a urethane (meth)acrylate resin (A), a water reducing agent (B), and an aggregate (C). The urethane (meth)acrylate resin mortar composition according to the present embodiment preferably further contains a metal-containing compound (D) and a thiol compound having a specific skeleton (E). In this specification, "(meth)acrylate" means "acrylate or methacrylate." "Urethane (meth)acrylate resin" means "urethane acrylate resin or urethane methacrylate resin."
[0016] <Urethane (meth)acrylate resin (A)> An example of the urethane (meth)acrylate resin (A) according to the present embodiment is a resin obtained by reacting hydroxyl groups or isocyanato groups at both ends of a polyurethane obtained by reacting an isocyanate with a polyhydric alcohol with (meth)acrylic acid. The urethane (meth)acrylate resin (A) preferably has a number average molecular weight of 1,000 to 50,000 from the viewpoint of sagging resistance.
[0017] [Isocyanate] Examples of the isocyanate include 2,4-tolylene diisocyanate and its isomers, diphenylmethane diisocyanate, hexamethylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, dicyclohexylmethane diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, Burnock (registered trademark) D-750, CRISBON (registered trademark) NK (trade name; manufactured by Dainippon Ink and Chemicals, Inc.), Desmodur (registered trademark) L (trade name; manufactured by Sumitomo Bayer), Coronate L (trade name; manufactured by Nippon Polyurethane Co., Ltd.), Takenate D102 (trade name; manufactured by Takeda Pharmaceutical Co., Ltd.), Isonate 143L (trade name; manufactured by Mitsubishi Chemical Corporation), and Duranate (registered trademark) series (trade name; manufactured by Asahi Kasei Chemical Co., Ltd.). These polyisocyanates may be used alone or in combination of two or more.
[0018] [Polyhydric alcohol] Examples of the polyhydric alcohol include ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, 2-methyl-1,3-propanediol, 1,3-butanediol, an adduct of bisphenol A with propylene oxide or ethylene oxide, 1,2,3,4-tetrahydroxybutane, glycerin, trimethylolpropane, 1,3-butanediol, 1,2-cyclohexane glycol, 1,3-cyclohexane glycol, 1,4-cyclohexane glycol, paraxylene glycol, bicyclohexyl-4,4-diol, 2,6-decalin glycol, 2,7-decalin glycol, etc. These polyhydric alcohols may be used alone or in combination of two or more.
[0019] [(Meth)acrylic acid] Examples of the (meth)acrylic acid include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, di(meth)acrylate of tris(hydroxyethyl)isocyanuric acid, pentaerythritol tri(meth)acrylate, glycerin (mono)(meth)acrylate, and the Blemmer (registered trademark) series (product name; manufactured by NOF Corp.). These hydroxyl group-containing (meth)acrylic compounds may be used alone or in combination of two or more.
[0020] <Catalyst> Examples of the catalyst include compounds containing tertiary nitrogen, such as triethylamine, pyridine derivatives, and imidazole derivatives; amine salts, such as tetramethylammonium chloride and triethylamine; phosphorus compounds, such as trimethylphosphine and triphenylphosphine; and tin compounds, such as dibutyltin dilaurate.
[0021] <Radical polymerizable unsaturated monomer (M)> The resin mortar composition of the present embodiment may further contain a radically polymerizable unsaturated monomer (M) in addition to the urethane (meth)acrylate resin (A). The radically polymerizable unsaturated monomer is not particularly limited, but is preferably one having a vinyl group or a (meth)acryloyl group. Specific examples of monomers having a vinyl group include styrene, p-chlorostyrene, vinyltoluene, α-methylstyrene, dichlorostyrene, divinylbenzene, tert-butylstyrene, vinyl acetate, diallyl phthalate, and triallyl isocyanurate.
[0022] Specific examples of monomers having a (meth)acryloyl group include (meth)acrylic acid esters, etc. Specifically, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, stearyl (meth)acrylate, tridecyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, phenoxyethyl methacrylate, 2-hydroxyethyl methacrylate, ethylene glycol monomethyl ether (meth)acrylate, ethylene glycol monoethyl ether (meth)acrylate, ethylene glycol monobutyl ether (meth)acrylate, ethylene glycol monohexyl ... ) acrylate, ethylene glycol mono 2-ethylhexyl ether (meth)acrylate, diethylene glycol monomethyl ether (meth)acrylate, diethylene glycol monoethyl ether (meth)acrylate, diethylene glycol monobutyl ether (meth)acrylate, diethylene glycol monohexyl ether (meth)acrylate, diethylene glycol mono 2-ethylhexyl ether (meth)acrylate, neopentyl glycol di(meth)acrylate, PTMG dimethacrylate, 1,3-butylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 2-hydroxy-1,3-dimethacryloxypropane, 2,2-bis[4-(methacryloylethoxy)phenyl]propane, 2,2-bis[4-(methacryloxy-diethoxy)phenyl]propane, 2,Examples of the acrylates include 2-bis[4-(methacryloxy-polyethoxy)phenyl]propane, tetraethylene glycol diacrylate, bisphenol A EO-modified (n=2) diacrylate, isocyanuric acid EO-modified (n=3) diacrylate, pentaerythritol diacrylate monostearate, dicyclopentenyl acrylate, dicyclopentenyloxyethyl acrylate, tricyclodecanyl (meth)acrylate, and tris(2-hydroxyethyl)isocyanuracrylate.
[0023] Further, examples of polyfunctional (meth)acrylic acid esters include alkanediol di(meth)acrylates such as ethylene glycol di(meth)acrylate, 1,2-propylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate; diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, and triethylene glycol (meth)acrylate. polyoxyalkylene glycol di(meth)acrylates such as tetraethylene glycol di(meth)acrylate and polyethylene glycol (meth)acrylate; trimethylolpropane di(meth)acrylate, glycerin di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and the like.
[0024] Furthermore, the following compounds can also be used as the radical polymerizable unsaturated monomer.Specific examples include divinylbenzene, diallyl phthalate, triallyl phthalate, triallyl cyanurate, triallyl isocyanurate, allyl (meth)acrylate, diallyl fumarate, allyl methacrylate, vinylbenzyl butyl ether, vinylbenzyl hexyl ether, vinylbenzyl octyl ether, vinylbenzyl (2-ethylhexyl) ether, vinylbenzyl (β-methoxymethyl) ether, vinylbenzyl (n-butoxypropyl) ether, vinylbenzyl cyclohexyl ether, vinylbenzyl (β-phenoxyethyl) ether, vinylbenzyl dicyclopentenyl ether, vinylbenzyl dicyclopentenyloxyethyl ether, vinylbenzyl dicyclopentenyl methyl ether, and divinylbenzyl ether. In addition to the above, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate and the like can also be used. As the radical polymerizable unsaturated monomer (M), dicyclopentenyloxyethyl methacrylate and dicyclopentanyl methacrylate are preferred from the viewpoint of compatibility with urethane methacrylate and aggregates. If compatibility is poor, the resin mortar may separate and drip. These may be used alone or in combination of two or more.
[0025] The radical polymerizable unsaturated monomer (M) can be used to reduce the viscosity of the resin mortar composition of the present embodiment and improve hardness, strength, chemical resistance, water resistance, etc., but if the content is too high, it may lead to deterioration of the cured product or environmental pollution. Therefore, the content of the radical polymerizable unsaturated monomer is preferably 90 mass% or less.
[0026] The urethane (meth)acrylate resin mortar composition may contain residual catalysts and polymerization inhibitors used in synthesizing the urethane (meth)acrylate resin (A). Examples of the catalyst include compounds containing tertiary nitrogen, such as triethylamine, pyridine derivatives, and imidazole derivatives; amine salts, such as tetramethylammonium chloride and triethylamine; and phosphorus compounds, such as trimethylphosphine and triphenylphosphine. Examples of the polymerization inhibitor include hydroquinone, methylhydroquinone, and phenothiazine. When the catalyst or polymerization inhibitor remains in the urethane (meth)acrylate resin mortar composition, the amount thereof is preferably 0.001 to 2 parts by mass, respectively, per 100 parts by mass of the vinyl ester resin and the unsaturated polyester resin in total.
[0027] In the urethane (meth)acrylate resin mortar composition, the content of the urethane (meth)acrylate resin (A) is preferably 5 to 99.9 mass%, more preferably 10 to 80 mass%, even more preferably 15 to 60 mass%, and even more preferably 20 to 50 mass%. When the content of the urethane (meth)acrylate resin (A) in the urethane (meth)acrylate resin mortar composition is within the above range, the hardness of the cured product is further improved.
[0028] <Metal-containing compounds (D)> The resin mortar composition of this embodiment can use one or more metal-containing compounds (D) selected from metal soaps (D1) and metal complexes (D2) having a β-diketone skeleton as a curing accelerator. The metal soap (D1) in this embodiment refers to a salt of a long-chain fatty acid or an organic acid other than a long-chain fatty acid and a metal element other than potassium and sodium. The metal complex (D2) having a β-diketone skeleton in this embodiment refers to a complex in which a compound having a structure in which one carbon atom is between two carbonyl groups is coordinated to a metal element.
[0029] The content of the metal-containing compound (D) in the urethane (meth)acrylate resin mortar composition in terms of metal components is preferably 0.001 to 5 parts by mass, more preferably 0.002 to 4 parts by mass, and even more preferably 0.005 to 3 parts by mass, based on 100 parts by mass of the above-mentioned urethane (meth)acrylate resin (A). When the content of the metal-containing compound (D) in terms of metal components is within the above range, curing proceeds quickly even in water and in a humid atmosphere.
[0030] [Metal soap (D1)] The long-chain fatty acid in the metal soap (D1) is not particularly limited, but is preferably, for example, a fatty acid having 6 to 30 carbon atoms. Specifically, preferred are linear or cyclic saturated fatty acids such as octanoic acids such as heptanoic acid and 2-ethylhexanoic acid, nonanoic acid, decanoic acid, neodecanoic acid, undecanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, octadecanoic acid, eicosanoic acid, docosanoic acid, tetracosanoic acid, hexacosanoic acid, octacosanoic acid, triacontanoic acid, and naphthenic acid, and unsaturated fatty acids such as oleic acid, linoleic acid, and linolenic acid. Other examples include rosin acid, linseed oil fatty acid, soybean oil fatty acid, tall oil acid, and the like.
[0031] The organic acid other than the long-chain fatty acid in the metal soap (D1) is not particularly limited, but is preferably a weak acid compound having a carboxy group, a hydroxy group, or an enol group, which is soluble in an organic solvent. Examples of compounds having a carboxy group include carboxylic acids such as formic acid, acetic acid, and oxalic acid; hydroxy acids such as citric acid, bile acid, sugar acid, 12-hydroxystearic acid, hydroxycinnamic acid, and folic acid; amino acids such as alanine and arginine; and aromatic acids such as benzoic acid and phthalic acid. Examples of compounds having a hydroxy group or an enol group include ascorbic acid, alpha acid, imido acid, erythorbic acid, croconic acid, kojic acid, squaric acid, sulfinic acid, teichoic acid, dehydroacetic acid, delta acid, uric acid, hydroxamic acid, humic acid, fulvic acid, and phosphonic acid. Among these, long-chain fatty acids are preferred, linear or cyclic saturated fatty acids having 6 to 16 carbon atoms, or unsaturated fatty acids having 6 to 16 carbon atoms are more preferred, octanoic acid, 2-ethylhexanoic acid, and naphthenic acid are even more preferred, and 2-ethylhexanoic acid and naphthenic acid are even more preferred.
[0032] Examples of the metal element constituting the metal soap (D1) include metal elements of Groups 1 and 2 such as lithium, magnesium, calcium, and barium (excluding potassium and sodium); metal elements of Groups 3 to 12 such as titanium, zirconium, vanadium, manganese, iron, ruthenium, cobalt, rhodium, nickel, palladium, platinum, copper, silver, gold, and zinc; metal elements of Groups 13 and 14 such as aluminum, indium, tin, and lead; rare earth metal elements such as neodymium and cerium; and bismuth. In this embodiment, metal elements of Groups 2 to 12 are preferred, zirconium, barium, vanadium, manganese, iron, cobalt, copper, titanium, bismuth, calcium, lead, tin and zinc are more preferred, zirconium, manganese, iron, cobalt, copper, titanium, bismuth, calcium, lead, tin and zinc are even more preferred, and zirconium, manganese, cobalt, bismuth and calcium are even more preferred.
[0033] Specific examples of the metal soap (D1) include zirconium octylate, manganese octylate, cobalt octylate, bismuth octylate, calcium octylate, zinc octylate, vanadium octylate, lead octylate, tin octylate, cobalt naphthenate, copper naphthenate, barium naphthenate, bismuth naphthenate, calcium naphthenate, lead naphthenate, and tin naphthenate, and among these, zirconium octylate, manganese octylate, cobalt octylate, bismuth octylate, calcium octylate, lead octylate, tin octylate, bismuth naphthenate, calcium naphthenate, lead naphthenate, and tin naphthenate are more preferred. Among these, manganese octylate and cobalt octylate are particularly preferred. A specific example of cobalt octylate is cobalt hexoate (cobalt content in the total product: 8% by mass, molecular weight: 345.34) manufactured by Toei Kako Co., Ltd. A specific example of manganese octylate is manganese hexoate (manganese content in the total product: 8% by mass, molecular weight: 341.35) manufactured by Toei Kako Co., Ltd.
[0034] [Metal complexes with β-diketone skeletons (D2)] Metal complex (D2) having a β-diketone skeleton (hereinafter also referred to as "metal complex (D2)"). Examples of the metal complex (D2) include those in which a metal is complexed with acetylacetone, ethyl acetoacetate, benzoylacetone, or the like, and these metal complexes (D2) also exhibit the same functions as the metal soap (D1). Examples of the metal element constituting the metal complex (D2) include the same metal elements as those in the metal soap (D1).
[0035] Specific examples of the metal complex (D2) include zirconium acetylacetonate, vanadium acetylacetonate, cobalt acetylacetonate, titanium acetylacetonate, titanium dibutoxybis(acetylacetonate), iron acetylacetonate, and cobalt ethyl acetoacetate. Among these, zirconium acetylacetonate, titanium acetylacetonate, and titanium dibutoxybis(acetylacetonate) are more preferable.
[0036] <Thiol Compound (E)> The resin mortar composition of this embodiment may contain one or more thiol compounds (E) selected from secondary thiol compounds (E-1) and tertiary thiol compounds (E-2). In this embodiment, the thiol compound (E) functions as a curing accelerator and is presumed to coordinate near the metal of the metal-containing compound (D) to prevent the metal from being deactivated by water. The thiol compound (E) used in this embodiment is not particularly limited as long as it has one or more mercapto groups (hereinafter, each may be referred to as a "secondary mercapto group" and a "tertiary mercapto group") bonded to a secondary or tertiary carbon atom in the molecule, but from the viewpoint of rapidly proceeding with curing even in water and from the viewpoint of preventing the metal of the metal-containing compound (D) from being deactivated by water, a polyfunctional thiol, which is a compound having two or more secondary or tertiary mercapto groups in the molecule, is preferred, and among them, a bifunctional thiol, which is a compound having two secondary or tertiary mercapto groups in the molecule, is preferred. In addition, a secondary thiol compound (E-1) is more preferred than a tertiary thiol compound (E-2). As used herein, "polyfunctional thiol" refers to a thiol compound having two or more mercapto groups as functional groups, and "bifunctional thiol" refers to a thiol compound having two mercapto groups as functional groups.
[0037] The compound having two or more secondary or tertiary mercapto groups in the molecule is not particularly limited, but for example, a compound having at least one structure represented by the following formula (Q) and having two or more secondary or tertiary mercapto groups in the molecule including the mercapto group in the structure represented by the following formula (Q) is preferred.
[0038] [ka]
[0039] (In formula (Q), R 1 is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or an aromatic group having 6 to 18 carbon atoms; R2 is an alkyl group having 1 to 10 carbon atoms or an aromatic group having 6 to 18 carbon atoms, and * indicates that it is linked to an arbitrary organic group. a is an integer of 0 to 2.)
[0040] [Secondary thiol compound (E-1)] When the thiol compound (E) having the structure represented by the formula (Q) is a secondary thiol compound (E-1), specific examples thereof include 3-mercaptobutyric acid, di(1-mercaptoethyl) 3-mercaptophthalate, di(2-mercaptopropyl) phthalate, di(3-mercaptobutyl) phthalate, ethylene glycol bis(3-mercaptobutyrate), propylene glycol bis(3-mercaptobutyrate), diethylene glycol bis(3-mercaptobutyrate), butanediol bis(3-mercaptobutyrate), octanediol bis(3-mercaptobutyrate), and the like. mercaptobutyrate), trimethylolethane tris(3-mercaptobutyrate), trimethylolpropane tris(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptobutyrate), dipentaerythritol hexakis(3-mercaptobutyrate), ethylene glycol bis(2-mercaptopropionate), propylene glycol bis(2-mercaptopropionate), diethylene glycol bis(2-mercaptopropionate), butanediol bis(2-mercaptopropionate), octanedio ethanol bis(2-mercaptopropionate), trimethylolpropane tris(2-mercaptopropionate), pentaerythritol tetrakis(2-mercaptopropionate), dipentaerythritol hexakis(2-mercaptopropionate), ethylene glycol bis(4-mercaptovalerate), diethylene glycol bis(4-mercaptovalerate), butanediol bis(4-mercaptovalerate), octanediol bis(4-mercaptovalerate), trimethylolpropane tris(4-mercaptovalerate), Pentaerythritol tetrakis(4-mercaptovalerate), dipentaerythritol hexakis(4-mercaptovalerate), ethylene glycol bis(3-mercaptovalerate), propylene glycol bis(3-mercaptovalerate), diethylene glycol bis(3-mercaptovalerate), butanediol bis(3-mercaptovalerate), octanediol bis(3-mercaptovalerate), trimethylolpropane tris(3-mercaptovalerate), pentaerythritol tetrakis(3-mercaptovalerate),Dipentaerythritol hexakis(3-mercaptovalerate), hydrogenated bisphenol A bis(3-mercaptobutyrate), bisphenol A dihydroxyethyl ether-3-mercaptobutyrate, 4,4'-(9-fluorenylidene)bis(2-phenoxyethyl(3-mercaptobutyrate)), ethylene glycol bis(3-mercapto-3-phenylpropionate), propylene glycol bis(3-mercapto-3-phenylpropionate), diethylene glycol bis(3-mercapto-3-phenylpropionate), lopionate), butanediol bis(3-mercapto-3-phenylpropionate), octanediol bis(3-mercapto-3-phenylpropionate), trimethylolpropane tris(3-mercapto-3-phenylpropionate), tris-2-(3-mercapto-3-phenylpropionate)ethyl isocyanurate, pentaerythritol tetrakis(3-mercapto-3-phenylpropionate), dipentaerythritol hexakis(3-mercapto-3-phenylpropionate), etc.
[0041] Among the secondary thiol compounds (E-1), commercially available compounds having two or more secondary mercapto groups in the molecule include 1,4-bis(3-mercaptobutyryloxy)butane (manufactured by Resonac Co., Ltd., KarenzMT (registered trademark) BD1), pentaerythritol tetrakis(3-mercaptobutyrate) (manufactured by Resonac Co., Ltd., KarenzMT (registered trademark) PE1), 1,3,5-tris[2-(3-mercaptobutyryloxyethyl)]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione (manufactured by Resonac Co., Ltd., KarenzMT (registered trademark) NR1), trimethylolethane tris(3-mercaptobutyrate) (manufactured by Resonac Co., Ltd., TEMB), and trimethylolpropane tris(3-mercaptobutyrate) (manufactured by Resonac Co., Ltd., TPMB), and it is preferable to use one or more of these. Among these, 1,4-bis(3-mercaptobutyryloxy)butane (manufactured by Resonac Corporation, KarenzMT (registered trademark) BD1) is preferable.
[0042] [Tertiary thiol compound (E-2)] When the thiol compound (E) having a structure represented by the formula (Q) is a tertiary thiol compound (E-2), specific examples thereof include di(2-mercaptoisobutyl)phthalate, ethylene glycol bis(2-mercaptoisobutyrate), propylene glycol bis(2-mercaptoisobutyrate), diethylene glycol bis(2-mercaptoisobutyrate), butanediol bis(2-mercaptoisobutyrate), octanediol bis(2-mercaptoisobutyrate), trimethylolethane tris(2-mercaptoisobutyrate), trimethylolpropane tris(2-mercaptoisobutyrate), pentaerythritol tetrakis(2-mercaptoisobutyrate), dipentaerythritol hexakis(2-mercaptoisobutyrate), and the like. butylate), di(3-mercapto-3-methylbutyl)phthalate, ethylene glycol bis(3-mercapto-3-methylbutyrate), propylene glycol bis(3-mercapto-3-methylbutyrate), diethylene glycol bis(3-mercapto-3-methylbutyrate), butanediol bis(3-mercapto-3-methylbutyrate), octanediol bis(3-mercapto-3-methylbutyrate), trimethylolethane tris(3-mercapto-3-methylbutyrate), trimethylolpropane tris(3-mercapto-3-methylbutyrate), pentaerythritol tetrakis(3-mercapto-3-methylbutyrate), dipentaerythritol hexakis(3-mercapto-3-methylbutyrate), and the like.
[0043] The total amount of the thiol compound (E) in the urethane (meth)acrylate resin mortar composition of this embodiment is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 7 parts by mass, even more preferably 0.1 to 5 parts by mass, and even more preferably 0.2 to 4 parts by mass, based on 100 parts by mass of the urethane (meth)acrylate resin (A) described above. When the amount of the thiol compound (E) is 0.01 parts by mass or more, the curing function can be sufficiently obtained, and when it is 10 parts by mass or less, the curing proceeds quickly.
[0044] The total molar ratio [(E) / (D)] of the thiol compound (E) to the metal component of the metal-containing compound (D) is preferably 0.1 to 15, more preferably 0.3 to 10 in one aspect of this embodiment, still more preferably 0.6 to 8, and even more preferably 0.8 to 5, and in another aspect of this embodiment, more preferably 0.5 to 15, still more preferably 1 to 12, still more preferably 1.5 to 10, and even more preferably 2 to 9. When the molar ratio [(E) / (D)] is 0.1 or more, the thiol compound (E) can be sufficiently coordinated in the vicinity of the metal of the metal-containing compound (D), and when the molar ratio is 15 or less, the balance between the production cost and the effect is improved.
[0045] The thiol compound (E) may be used alone or in combination of two or more. When the secondary thiol compound (E-1) and the tertiary thiol compound (E-2) are used together, the molar ratio [(E-1) / (E-2)] of the two is preferably 0.001 to 1000, more preferably 1 to 10. When the molar ratio [(E-1) / (E-2)] is within the above range, the metal-containing compound (A) and the thiol compound (E) are stable in the urethane (meth)acrylate resin mortar composition, and disulfide compounds caused by bonds between the thiol compounds (E) as by-products are not generated. From the viewpoint of storing the urethane (meth)acrylate resin mortar composition with the metal-containing compound (D) and the thiol compound (E) in a stable state, it is preferable to use the secondary thiol compound (E-1) or the tertiary thiol compound (E-2) alone.
[0046] [Water reducing agent (B)] The urethane (meth)acrylate resin mortar composition of the present embodiment contains a usable water reducing agent (B) that can impart water reducing properties. As the water reducing agent, any known water reducing agent used in concrete, such as liquid or powder water reducing agents, AE water reducing agents, high-performance AE water reducing agents, etc., can be used without limitation. Examples of the water reducing agent (B) include high-performance water reducing agents such as naphthalene sulfonate formaldehyde condensates, melamine formaldehyde condensates, and styrene sulfonic acid copolymers, AE water reducing agents such as polycarboxylic acids and lignin sulfonic acids, and cement water reducing agents such as polystyrene sulfonic acid, naphthalene sulfonic acid, and melamine sulfonic acid. Among them, from the viewpoint of preventing a decrease in strength due to air entrainment, preferred are naphthalenesulfonate-formaldehyde condensates, melanin-formaldehyde condensates, styrenesulfonic acid copolymers, polystyrenesulfonic acid, naphthalenesulfonic acid, and melanin sulfonic acid, and more preferred are naphthalenesulfonate-formaldehyde condensates, melanin-formaldehyde condensates, and styrenesulfonic acid copolymers. The preferred content is 0.1 to 5 parts by mass, more preferably 0.2 to 3 parts by mass. Within the above content range, there is an effect of sagging resistance when applied to a vertical surface while maintaining workability.
[0047] The water reducing agent is preferably contained in an amount of 0.1 to 3.0% by mass in the urethane (meth)acrylate resin mortar composition.
[0048] [Aggregate (C)] The urethane (meth)acrylate resin mortar composition of the present embodiment includes aggregate (C). The aggregate (C) is not particularly limited, and can be one used in mortar or concrete. The aggregate (C) is not particularly limited, and can be, for example, cement, calcium carbonate, crushed stone, sandstone, kansui stone, marble, quartz, limestone, silica sand, silica stone, river sand, etc. In addition, from the viewpoint of weight reduction, lightweight aggregates such as sintered shale, silica balloon, and non-silica balloon perlite can also be used. Among these, silica sand is preferred, and silica sand No. 6 and silica sand No. 9 are more preferred.
[0049] As the cement, Portland cement (C2), other mixed cements, ultra-fast hardening cements, etc. can be used without any particular restrictions. As the Portland cement, various Portland cements such as low heat, moderate heat, normal, early strength, ultra early strength, and sulfate resistant Portland cements can be mentioned. As the mixed cements, blast furnace cement, fly ash cement, silica cement, etc. are mentioned. Among these, inexpensive Portland cement is preferable, and early strength and ultra early strength Portland cements are more preferable. As for these cements, the above-mentioned cements can be used alone or in any combination at any mixing ratio.
[0050] Calcium carbonate functions as an extender pigment in the coating film, being transparent and not hiding the coated surface (substrate surface), and has the effect of filling recesses, reducing paint costs, etc. An example of this calcium carbonate on the market is TM-2 (manufactured by Yukou Mining Co., Ltd.). Calcium carbonate has a specific particle size distribution, is highly dispersible, and is porous, so that it can reduce the specific gravity of the aggregate itself, making it less likely to sag, and improve film-forming properties.
[0051] Examples of silicate-based balloons include shirasu balloons, perlite, glass (silica) balloons, and fly ash balloons. Examples of non-silica-based balloons include alumina balloons, zirconia balloons, and carbon balloons. Specific examples of perlite include Perlite FL-0 (trade name, manufactured by Fuyo Perlite Co., Ltd.), Hardlite B-03, Hardlite B-04, and Hardlite B-05 (all trade names, manufactured by Showa Chemical Industry Co., Ltd.).
[0052] The content of aggregate (C) in the urethane (meth)acrylate resin mortar composition of the present embodiment is not particularly limited, but is 330 to 800 parts by mass, preferably 350 to 800 parts by mass, and more preferably 370 to 450 parts by mass, relative to 100 parts by mass of the urethane (meth)acrylate resin (A). In particular, if the content of aggregate is 800 parts by mass or less, practical fluidity can be ensured. In addition, if the content of aggregate is 330 parts by mass or more, the amount of adhesion of the trowel is reduced, and a decrease in workability can be prevented.
[0053] When aggregate (C) contains cement, the content of cement in aggregate (C) is not particularly limited, but is preferably 1% by mass to 80% by mass, more preferably 5% by mass to 50% by mass, and even more preferably 5% by mass to 30% by mass, based on 100% by mass of aggregate (C). In particular, if the content of cement is 1% by mass or more, the particle size distribution of the aggregate can be optimized and practical fluidity can be ensured. Also, if the content of cement is 80% by mass or less, stickiness due to deterioration of fluidity can be prevented.
[0054] [Radical polymerization initiator (G)] The urethane (meth)acrylate resin mortar composition of the present embodiment preferably contains a radical polymerization initiator (G) as a curing agent. The radical polymerization initiator (G) may be a thermal radical polymerization initiator (G1) or a photoradical polymerization initiator (G2). Among them, the thermal radical polymerization initiator (G1) is preferred. Examples of the thermal radical polymerization initiator (G1) include diacyl peroxides such as benzoyl peroxide, peroxyesters such as tert-butyl peroxybenzoate, hydroperoxides (RCOOH, hydroperoxides) such as cumene hydroperoxide (CHP), diisopropylbenzene hydroperoxide, tert-butyl hydroperoxide, and paramenthane hydroperoxide, dialkyl peroxides such as dicumyl peroxide, ketone peroxides such as methyl ethyl ketone peroxide and acetylacetone peroxide, peroxyketals, alkyl peresters, and percarbonates. Among these, hydroperoxide radical polymerization initiators (RCOOH) (also simply referred to as hydroperoxides) are preferred, and cumene hydroperoxides (CHP) such as Percumyl (registered trademark) H-80 manufactured by NOF Corp. and diisopropylbenzene hydroperoxides such as Percumyl (registered trademark) P manufactured by NOF Corp. are more preferred.
[0055] Examples of the photoradical polymerization initiator (G2) include benzoin ethers such as benzoin alkyl ethers, benzophenones such as benzophenone, benzil, and methyl orthobenzoyl benzoate, acetophenones such as benzil dimethyl ketal, 2,2-diethoxyacetophenone, 2-hydroxy-2-methylpropiophenone, 4-isopropyl-2-hydroxy-2-methylpropiophenone, and 1,1-dichloroacetophenone, and thioxanthones such as 2-chlorothioxanthone, 2-methylthioxanthone, and 2-isopropylthioxanthone.
[0056] Examples of the photoradical polymerization initiator (G2) having sensitivity from ultraviolet light to the visible light region include known initiators such as acetophenone-based, benzyl ketal-based, and (bis)acylphosphine oxide-based initiators. Specifically, there are 2-hydroxy-2-methyl-1-phenylpropan-1-one (trade name: Darocur 1173, manufactured by Ciba Specialty Chemicals Co., Ltd.) and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide (manufactured by Ciba Specialty Chemicals Co., Ltd.) mixed in a ratio of 75% / 25% (trade name: Irgacure-1700, manufactured by Ciba Specialty Chemicals Co., Ltd.); 1-hydroxycyclohexyl phenyl Ketone (product name: Irgacure 184, manufactured by Chiba Specialty Chemicals Co., Ltd.) and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide (product name: Irgacure 1800, manufactured by Chiba Specialty Chemicals Co., Ltd.) were mixed in a ratio of 75% / 25% to produce Irgacure 1800 (manufactured by Chiba Specialty Chemicals Co., Ltd.), and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (product name: Irgacure 819, manufactured by Chiba Specialty Chemicals Co., Ltd.) were mixed in a ratio of 50% / 50% to produce Irgacure 1850 (manufactured by Chiba Specialty Chemicals Co., Ltd.); bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (product name: Irgacure 819, manufactured by Chiba Specialty Chemicals Co., Ltd.); 2,4,6-trimethylbenzoyldiphenylphosphine oxide (product name: Lucirin TPO, manufactured by BASF Ltd.); Darocur 4265, which is a 50% / 50% mixture of 2-hydroxy-2-methyl-1-phenylpropan-1-one (trade name: Darocur 1173, manufactured by Chiba Specialty Chemicals Co., Ltd.) and 2,4,6-trimethylbenzoyldiphenylphosphine oxide (trade name: Lucirin TPO, manufactured by BASF Ltd.).
[0057] Examples of the photoradical polymerization initiator (G2) having photosensitivity in the visible light region include camphorquinone, benzyltrimethylbenzoyldiphenylphosphinoxide, methylthioxanthone, and dicyclopentadiethyltitanium-di(pentafluorophenyl). These radical polymerization initiators (G) may be used alone or in combination of two or more. In order to support the main reaction of either heat curing or photocuring, the other reaction may be introduced, and the heat radical polymerization initiator (G1) and the photoradical polymerization initiator (G2) may be used in combination as necessary.
[0058] In addition, depending on the molding conditions, they can also be used in composite forms such as organic peroxide / dye system, diphenyl iodide salt / dye system, imidazole / keto compound, hexaarylbiimidazole compound / hydrogen donor compound, mercaptobenzothiazole / thiopyrylium salt, metal arene / cyanine dye, and hexaarylbiimidazole / radical generator.
[0059] When the urethane (meth)acrylate resin mortar composition of the present embodiment contains a radical polymerization initiator (G), the content thereof is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 8.0 parts by mass, and even more preferably 0.3 to 5.0 parts by mass, relative to 100 parts by mass of the urethane (meth)acrylate resin (A).
[0060] [Cure accelerator] The urethane (meth)acrylate resin mortar composition of the present embodiment may contain a curing accelerator other than the metal-containing compound (D) and the thiol compound (E) for the purpose of improving the curing properties. Examples of the curing accelerator other than the metal-containing compound (D) and the thiol compound (E) include amines, specifically, aniline, N,N-dimethylaniline, N,N-diethylaniline, p-toluidine, N,N-dimethyl-p-toluidine, N,N-bis(2-hydroxyethyl)-p-toluidine, 4-(N,N-dimethylamino)benzaldehyde, 4-[N,N-bis(2-hydroxyethyl)amino]benzaldehyde, 4-(N-methyl-N-hydrazine), Examples of the amines that can be used include N,N-substituted anilines such as N,N-bis(hydroxyethylamino)benzaldehyde, N,N-bis(2-hydroxypropyl)-p-toluidine, N-ethyl-m-toluidine, triethanolamine, m-toluidine, diethylenetriamine, pyridine, phenylmorpholine, piperidine, N,N-bis(hydroxyethyl)aniline, and diethanolaniline, N,N-substituted-p-toluidines, and 4-(N,N-substituted amino)benzaldehyde. When the urethane (meth)acrylate resin mortar composition of this embodiment contains a curing accelerator, the content thereof is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, and even more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the urethane (meth)acrylate resin (A).
[0061] Fiber The urethane (meth)acrylate resin mortar composition of the present embodiment may contain fibers as necessary. Specific examples of fibers that can be used in the present embodiment include glass fibers, carbon fibers, vinylon fibers, nylon fibers, aramid fibers, polyolefin fibers, acrylic fibers, polyester fibers such as polyethylene terephthalate fibers, cellulose fibers, metal fibers such as steel fibers, and ceramic fibers such as alumina fibers.
[0062] Polyolefin fibers currently available on the market include polyethylene-based products with trade names such as Chemivest (registered trademark) FDSS-2 (average fiber length 0.6 mm), Chemivest (registered trademark) FDSS-5 (average fiber length 0.1 mm), Chemivest (registered trademark) FDSS-25 (average fiber length 0.6 mm, hydrophilized product), and Chemivest (registered trademark) FDSS-50 (average fiber length 0.1 mm, hydrophilized product) (all manufactured by Mitsui Petrochemical Industries, Ltd.).
[0063] The carbon fiber is not particularly limited, and any known carbon fiber can be used. Examples include polyacrylonitrile-based (PAN-based) carbon fiber, rayon-based carbon fiber, pitch-based carbon fiber, etc. The carbon fibers may be used alone or in combination of two or more. From the viewpoint of low cost and good mechanical properties, it is preferable to use PAN-based carbon fiber. Such carbon fibers are commercially available. As the carbon fiber, carbon fiber reinforced plastic (CFRP) may be used.
[0064] The diameter of the carbon fibers is preferably 3 to 15 μm, and more preferably 5 to 10 μm. The length of the carbon fiber is usually 5 to 100 mm. In this embodiment, the carbon fiber may be cut to a length of 10.0 mm to 100.0 mm, or further to a length of 12.5 mm to 50.0 mm before use.
[0065] These fibers are preferably used in the form of a fiber structure, biaxial mesh, or triaxial mesh selected from plain weave, satin weave, nonwoven fabric, mat, roving, chop, knit, braid, and composite structures thereof, etc. For example, the fiber structure can be impregnated with a radical polymerizable composition, and optionally prepolymerized to form a prepreg, before use. As the mesh, for example, a biaxial mesh or a triaxial mesh is used. The length of one side of a square of the biaxial mesh (mesh size) and the length of one side of an equilateral triangle of the triaxial mesh (mesh size) are each preferably 5 mm or more, more preferably 10 to 20 mm. By using a biaxial mesh or a triaxial mesh, a hardening material for preventing spalling of concrete can be obtained that is lightweight and has excellent economic efficiency, workability, and durability. These fibers are preferably used when reinforcing coating film performance such as concrete spalling prevention and FRP waterproofing, or when producing FRP molded products. For applications such as preventing concrete spalling, glass fibers and cellulose fibers, which have excellent transparency among fibers, are preferred because they allow the deterioration state of the base to be visually inspected from the outside.
[0066] The content of such fibers is preferably 0.3 to 200 parts by mass, more preferably 0.5 to 100 parts by mass, and further preferably 1.0 to 50 parts by mass, relative to 100 parts by mass of the urethane (meth)acrylate resin (A).
[0067] [Polymerization inhibitor (I)] The urethane (meth)acrylate resin mortar composition of the present embodiment may contain a polymerization inhibitor (I) from the viewpoint of suppressing excessive polymerization of the urethane methacrylate (A) and controlling the reaction rate. Examples of the polymerization inhibitor (I) include known inhibitors such as hydroquinone, methylhydroquinone, phenothiazine, catechol, and 4-tert-butylcatechol. When the urethane (meth)acrylate resin mortar composition contains a polymerization inhibitor (I), the amount thereof is 0.0001 to 10 parts by mass, more preferably 0.001 to 1 part by mass, per 100 parts by mass of the urethane (meth)acrylate resin (A).
[0068] [Cure retarder (J)] The urethane (meth)acrylate resin mortar composition of the present embodiment may contain a curing retarder for the purpose of delaying the curing of the urethane methacrylate resin (A). Examples of the curing retarder include free radical curing retarders, such as TEMPO derivatives, such as 2,2,6,6-tetramethylpiperidine 1-oxyl free radical (TEMPO), 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl free radical (4H-TEMPO), and 4-oxo-2,2,6,6-tetramethylpiperidine 1-oxyl free radical (4-Oxo-TEMPO). Among these, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl free radical (4H-TEMPO) is preferred from the standpoint of cost and ease of handling. When the urethane (meth)acrylate resin mortar composition contains a hardening retarder (J), the amount thereof is preferably 0.0001 to 10 parts by mass, more preferably 0.001 to 1 part by mass, per 100 parts by mass of the urethane (meth)acrylate resin (A).
[0069] [Other components (K)] The urethane (meth)acrylate resin mortar composition of the present embodiment may contain components other than the above components, as long as they do not significantly impair the strength expression or acid resistance of the hardened body. Examples of components that can be contained include hydraulic inorganic substances such as calcium sulfate and pozzolanic substances, as well as admixtures that can be used in mortar or concrete to impart properties such as setting adjustment, hardening acceleration, hardening retardation, thickening, water retention, defoaming, water repellency, and waterproofing, and admixtures that can be used in mortar or concrete, such as fibers made of materials such as metals, polymers, and carbon, pigments, extenders, foaming agents, and clay minerals such as zeolites. Examples of components that can be contained include coupling agents, plasticizers, anion fixing components, solvents, polyisocyanate compounds, surfactants, wetting and dispersing agents, waxes, and thixotropic agents (K1).
[0070] The thixotropic agent (K1) may be an inorganic thixotropic agent or an organic thixotropic agent. The organic thixotropic agent may be a hydrogenated castor oil type, an amide type, an oxidized polyethylene type, a vegetable oil polymerized oil type, a surfactant type, or a composite type using these in combination. Specific examples include DISPARLON (registered trademark) 6900-20X (Kusumoto Chemical Co., Ltd.). In addition, examples of inorganic thixotropic agents include silica and bentonite, and examples of hydrophobic agents include Reolosil (registered trademark) PM-20L (fumed silica manufactured by Tokuyama Corporation), Aerosil (registered trademark) AEROSIL R-106 (Nippon Aerosil Co., Ltd.), etc., and examples of hydrophilic agents include Aerosil (registered trademark) AEROSIL-200 (Nippon Aerosil Co., Ltd.), etc. From the viewpoint of further improving the thixotropy, a thixotropic modifier such as BYK (registered trademark)-R605 or BYK (registered trademark)-R606 (manufactured by BYK Japan KK) may also be suitably used in which hydrophilic calcined silica is added. When the urethane (meth)acrylate resin mortar composition of the present embodiment contains a thixotropic agent (K1), the amount thereof is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, per 100 parts by mass of the urethane (meth)acrylate resin (A). In addition, when the urethane (meth)acrylate resin mortar composition contains a thixotropic agent (K1), the content of the thixotropic agent (K1) is preferably 0.1% by mass to 10% by mass, more preferably 0.3% by mass to 5% by mass, based on the total of the aggregate (C) and the thixotropic agent (K1) being 100% by mass. In particular, if the content of the thixotropic agent (K1) is 0.1% by mass or more, sagging resistance can be obtained when the composition is applied to a vertical surface. In addition, if the content of the thixotropic agent (K1) is 10% by mass or less, the deterioration of workability due to thickening can be prevented.
[0071] <Coupling Agent> The urethane (meth)acrylate resin mortar composition of the present embodiment may contain a coupling agent for the purpose of improving processability and adhesion to a substrate, etc. Examples of the coupling agent include known silane-based coupling agents, titanate-based coupling agents, and aluminum-based coupling agents. Examples of such coupling agents include R 3 -Si(OR 4 ) 3 Examples of the silane coupling agent include those represented by the formula: 3 Examples of the alkyl group include an aminopropyl group, a glycidyloxy group, a methacryloxy group, an N-phenylaminopropyl group, a mercapto group, and a vinyl group. 4 Examples of the alkyl group include a methyl group and an ethyl group. When the urethane (meth)acrylate resin mortar composition contains a coupling agent, the amount thereof is preferably 0.001 to 10 parts by mass relative to 100 parts by mass of the urethane (meth)acrylate resin (A).
[0072] <Plasticizer> The urethane (meth)acrylate resin mortar composition of the present embodiment may contain a plasticizer as required. The plasticizer is not particularly limited, and for the purpose of adjusting the physical properties and characteristics, for example, phthalate esters such as dibutyl phthalate, diheptyl phthalate, di(2-ethylhexyl) phthalate, and butyl benzyl phthalate; non-aromatic dibasic acid esters such as dioctyl adipate, dioctyl sebacate, dibutyl sebacate, and isodecyl succinate; aliphatic esters such as butyl oleate and methyl acetyl ricinoleate; polyalkylene glycol esters such as diethylene glycol dibenzoate, triethylene glycol dibenzoate, and pentaerythritol ester; phosphate esters such as tricresyl phosphate and tributyl phosphate; trimellitic acid esters; polystyrenes such as polystyrene and poly-α-methylstyrene; polybutadiene, polybutene, polyisobutylene, butadiene-acrylonitrile, and polychloroprene; chlorinated paraffins; hydrocarbon oils such as alkyl diphenyls and partially hydrogenated terphenyls; and process oils. Examples of the polyether polyols include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, and other polyether polyols, and derivatives in which the hydroxyl groups of these polyether polyols are converted to ester groups, ether groups, and the like; epoxy plasticizers such as epoxidized soybean oil and epoxy benzyl stearate; polyester plasticizers obtained from dibasic acids such as sebacic acid, adipic acid, azelaic acid, and phthalic acid, and dihydric alcohols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, and dipropylene glycol; and vinyl polymers obtained by polymerizing vinyl monomers such as acrylic plasticizers by various methods. Among them, it is preferable to add a polymer plasticizer which is a polymer having a number average molecular weight of 500 to 15,000, since it is possible to adjust the viscosity of the radical polymerizable composition and the mechanical properties such as tensile strength and elongation of the cured product obtained by curing the composition. Moreover, the polymer plasticizer is preferable because it can maintain the initial physical properties for a long period of time compared with the case where a low molecular weight plasticizer which is a plasticizer that does not contain a polymer component in the molecule is used. Although not limited, this polymer plasticizer may or may not have a functional group. The number average molecular weight of the polymer plasticizer is more preferably 800 to 10,000, and even more preferably 1,000 to 8,000. If the number average molecular weight is 500 or more, the plasticizer can be prevented from flowing out over time due to the influence of heat, rainfall, and water, and the initial physical properties can be maintained for a long period of time. If the number average molecular weight is 15,000 or less, the viscosity increase can be prevented, and sufficient workability can be ensured.
[0073] <Anion fixing component> In addition, hydrotalcites or hydrocalumites can be used to immobilize anions such as chloride ions. These hydrotalcites may be natural or synthetic, and may be used regardless of whether they have been surface-treated or have water of crystallization. For example, hydrotalcites represented by the following general formula (R)
[0074] M x Magnesium y ·Al Z CO 3 (OH) xr+2y+3z-2 mH 2 O (R)
[0075] (wherein M is an alkali metal or zinc, x is a number from 0 to 6, y is a number from 0 to 6, z is a number from 0.1 to 4, r is the valence of M, and m is the number of water of crystallization (0 to 100). The hydrocalumite may be a natural product or a synthetic product, and may be used regardless of whether it is surface-treated or has water of crystallization. For example, hydrocalumite represented by the following general formula (S) or (T):
[0076] 3CaO·Al 2 O 3 ·CaX 2 kH 2 O (S)
[0077] (X is a monovalent anion, k≦20)
[0078] 3CaO·Al 2 O 3 CaY kH 2 O (T)
[0079] (Y is a divalent anion, k≦20) Examples of the above-mentioned formulas are given below.
[0080] In addition, calumite contains nitrite ions (NO ) during the manufacturing process, which are believed to have the effect of inhibiting corrosion of reinforcing bars. 2 - ) is supported, but an example of an anion that can be supported is the nitrate ion (NO 3 - ), hydroxide ion (OH - ), oxalate ion (CH 3 COO - ), carbonate ion (CO 3 - ), sulfate ion (SO 4 2- ) etc.
[0081] These hydrotalcites or hydrocalumites may be used alone, but can also be used by being mixed into cement paste. When mixed with cement paste, the hydroxide ions (OH - ) or sulfate ions (SO 4 2- ) is expected to have various effects on the anion exchange reaction that is a characteristic of calumite. From the viewpoint of maintaining the exchange reaction with the targeted chloride ions, hydrocalumite that supports nitrite ions is preferable.
[0082] <Solvent> In the urethane (meth) acrylate resin mortar composition of this embodiment, a solvent can be blended as necessary. Examples of solvents that can be blended include aromatic hydrocarbon solvents such as toluene and xylene; ester solvents such as ethyl acetate, butyl acetate, amyl acetate, and cellosolve acetate; ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone, and diisobutyl ketone. These solvents may be used during the production of the polymer.
[0083] <J105 Surfactant〕 The urethane (meth) acrylate resin mortar composition of this embodiment may contain a surfactant. Examples of surfactants include anionic surfactants, nonionic surfactants, cationic surfactants, and amphoteric surfactants. These surfactants may be used alone or in combination of two or more. Among these surfactants, one or more selected from anionic surfactants and nonionic surfactants are preferred.
[0084] Examples of anionic surfactants include alkyl sulfate esters such as sodium lauryl sulfate and triethanolamine lauryl sulfate; polyoxyethylene alkyl ether sulfate esters such as sodium polyoxyethylene lauryl ether sulfate and triethanolamine polyoxyethylene alkyl ether sulfate; sulfonates such as dodecylbenzenesulfonic acid, sodium dodecylbenzenesulfonate, sodium alkylnaphthalenesulfonate, and sodium dialkylsulfosuccinate; fatty acid salts such as sodium stearate soap, potassium oleate soap, and potassium castor oil soap; naphthalenesulfonic acid formalin condensates, special polymer systems, and the like. Among these, sulfonates are preferred, sodium dialkylsulfosuccinate is more preferred, and sodium dioctylsulfosuccinate is even more preferred.
[0085] Examples of nonionic surfactants include polyoxyethylene alkyl ethers such as polyoxylauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, and polyoxyethylene oleyl ether; polyoxyethylene derivatives such as polyoxyethylene distyrenated phenyl ether, polyoxyethylene tribenzyl phenyl ether, and polyoxyethylene polyoxypropylene glycol; polyoxyalkylene alkyl ethers; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monopalmitate, and sorbitan monostearate; polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monolaurate, and polyoxyethylene sorbitan monopalmitate; polyoxyethylene sorbitol fatty acid esters such as polyoxyethylene sorbitan tetraoleate; and glycerin fatty acid esters such as glycerin monostearate and glycerin monooleate. Among these, polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, and polyoxyethylene alkyl ether are preferred. The HLB (Hydrophile-Lipophil Balance) of the nonionic surfactant is preferably 5 to 15, and more preferably 6 to 12.
[0086] When the urethane (meth)acrylate resin mortar composition contains a surfactant, the amount thereof is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 7 parts by mass, and even more preferably 0.1 to 5 parts by mass, per 100 parts by mass of the urethane (meth)acrylate resin (A).
[0087] [Wetting and dispersing agent] The urethane (meth)acrylate resin mortar composition of the present embodiment may contain, for example, a wetting and dispersing agent in order to improve the permeability into a wet or submerged repair site. Examples of wetting and dispersing agents include fluorine-based wetting and dispersing agents and silicone-based wetting and dispersing agents, which may be used alone or in combination of two or more kinds. Commercially available fluorine-based wetting and dispersing agents include Megafac (registered trademark) F176, Megafac (registered trademark) R08 (manufactured by Dainippon Ink and Chemicals, Inc.), PF656, PF6320 (manufactured by OMNOVA), Troysol S-366 (manufactured by Troy Chemical Co., Ltd.), Fluorad FC430 (manufactured by 3M Japan Ltd.), and polysiloxane polymer KP-341 (manufactured by Shin-Etsu Chemical Co., Ltd.). Commercially available silicone-based wetting and dispersing agents include BYK (registered trademark)-322, BYK (registered trademark)-377, BYK (registered trademark)-UV3570, BYK (registered trademark)-330, BYK (registered trademark)-302, BYK (registered trademark)-UV3500, BYK-306 (manufactured by BYK Japan KK), and polysiloxane polymer KP-341 (manufactured by Shin-Etsu Chemical Co., Ltd.).
[0088] The silicone-based wetting and dispersing agent preferably contains a compound represented by the following formula (U). [ka]
[0089] (In the formula, R 5 and R 6 each independently represents a hydrocarbon group having 1 to 12 carbon atoms which may contain an aromatic ring, or -(CH 2 ) 3 O(C 2 H 4 O) p (CH 2 CH(CH 3 )O) q R' represents an alkyl group having 1 to 12 carbon atoms, n is an integer of 1 to 200, p and q are each an integer, and q / p=0 to 10 is satisfied. In addition, examples of commercially available silicone-based wetting and dispersing agents containing the compound represented by formula (U) include BYK (registered trademark)-302 and BYK (registered trademark)-322 (manufactured by BYK Japan KK). When the urethane (meth)acrylate resin mortar composition of the present embodiment contains a wetting dispersant, the amount thereof is preferably 0.001 to 5 parts by mass, more preferably 0.01 to 2 parts by mass, per 100 parts by mass of the urethane (meth)acrylate resin (A).
[0090] 〔wax〕 The urethane (meth)acrylate resin mortar composition of the present embodiment may contain wax. Examples of waxes include paraffin waxes and polar waxes, which may be used alone or in combination of two or more kinds. The paraffin waxes may be any known wax having a variety of melting points. The polar waxes may be any wax having both polar and non-polar groups in its structure, and specific examples thereof include NPS (registered trademark)-8070, NPS (registered trademark)-9125 (manufactured by Nippon Seiro Co., Ltd.), Emanone (registered trademark) 3199, and Emanone (registered trademark) 3299 (manufactured by Kao Corporation). When the urethane (meth)acrylate resin mortar composition of the present embodiment contains a wax, the amount of the wax is preferably 0.05 to 4 parts by mass, more preferably 0.1 to 2.0 parts by mass, based on 100 parts by mass of the urethane (meth)acrylate resin (A). However, when the urethane (meth)acrylate resin mortar composition of the present embodiment is used in water, it is preferable not to use the wax because there is a risk of the wax dissolving in the water.
[0091] <Water> The urethane (meth)acrylate resin mortar composition of the present embodiment is preferably substantially free of water from the viewpoint of obtaining a practical level of strength. That is, when preparing the urethane (meth)acrylate resin mortar composition, it is preferable not to add water as a constituent of the composition. For example, the water content of the urethane (meth)acrylate resin mortar composition is preferably less than 0.25 parts by mass, more preferably 0.20 parts by mass or less, even more preferably 0.15 parts by mass or less, and most preferably 0.10 parts by mass or less, relative to 100 parts by mass of the urethane (meth)acrylate resin (A).
[0092] [Method for producing urethane (meth)acrylate resin mortar composition] The method for producing the urethane (meth)acrylate resin mortar composition of the present embodiment is not particularly limited, and may be a method known in the art. For example, the method may include a step of synthesizing a urethane (meth)acrylate resin (A), a step of blending and mixing a radical polymerizable unsaturated monomer (M), a metal-containing compound (D), a thiol compound (E) having a specific skeleton, and a radical polymerization initiator (G) with the urethane (meth)acrylate resin (A) as necessary, and a step of further mixing a water reducing agent (B) and an aggregate (C). In addition, a method for producing the urethane (meth)acrylate resin mortar composition of this embodiment can be exemplified by mixing the urethane (meth)acrylate resin (A) with a water reducing agent (B), aggregate (C), and, if necessary, a radical polymerizable unsaturated monomer (M), a metal-containing compound (D), a thiol compound having a specific skeleton (E), and a radical polymerization initiator (G).
[0093] The urethane (meth)acrylate resin mortar composition thus produced can be cured even at low temperatures, and is excellent in workability, early strength development and curing properties.
[0094] (Cured product of urethane (meth)acrylate resin mortar composition) The cured product of the urethane (meth)acrylate resin mortar composition of one embodiment of the present invention (which may also be referred to as the cured product of the urethane (meth)acrylate resin mortar composition of the present embodiment, or the cured product of the resin mortar composition of the present embodiment) is obtained by curing the above-mentioned urethane (meth)acrylate resin mortar composition of the present embodiment.
[0095] [Method of curing urethane (meth)acrylate resin mortar composition] When the urethane (meth)acrylate resin mortar composition of the present embodiment contains a thermal radical polymerization initiator (G1), an example of the curing method of the urethane (meth)acrylate resin mortar composition of the present embodiment is to apply the urethane (meth)acrylate resin mortar composition of the present embodiment to the surface of a substrate and cure it at room temperature. For example, the urethane (meth)acrylate resin mortar composition of the present embodiment is used as a cross-section repair material for inorganic structures. Examples of materials for the substrate include concrete, asphalt concrete, mortar, brick, wood, and metal, as well as thermosetting resins such as phenolic resin, epoxy resin, melamine resin, urea resin, unsaturated polyester resin, vinyl ester resin, alkyd resin, polyurethane, and polyimide; and thermoplastic resins such as polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyvinyl acetate, polyurethane, Teflon (registered trademark), ABS resin, AS resin, and acrylic resin.
[0096] When the urethane (meth)acrylate resin mortar composition of the present embodiment contains a photoradical polymerization initiator (C2), the timing of photocuring may be, for example, a method in which the urethane (meth)acrylate resin mortar composition is applied to a substrate and then photocured, or a method in which a sheet is prepared by prepolymerizing the urethane (meth)acrylate resin mortar composition in advance (also called B-stage or prepreg), and the sheet is attached to a substrate and then photocured.
[0097] The light source may be any light source having a spectral distribution in the photosensitive wavelength range of the photoradical polymerization initiator (C2), and may be, for example, sunlight, an ultraviolet lamp, a near-infrared lamp, a sodium lamp, a halogen lamp, a fluorescent lamp, a metal halide lamp, an LED, or the like. In addition, two or more types of photoradical polymerization initiators (C2) may be used in combination, and a wavelength cut filter may be used as the light source, or a specific wavelength of an LED may be used to selectively use the wavelengths required for preliminary polymerization and main polymerization. The wavelengths used for preliminary polymerization are preferably long wavelengths with low energy levels, and the degree of polymerization is easily controlled by using near-infrared light in particular. In this embodiment, ultraviolet light (ultraviolet rays) refers to light rays in the wavelength range of 280 to 380 nm, visible light (visible rays) refers to light in the wavelength range of 380 to 780 nm, and near-infrared light (near-infrared rays) refers to light in the wavelength range of 780 to 1200 nm. The irradiation time of the lamp required for preliminary polymerization cannot be generally specified because it is affected by the effective wavelength range, output, irradiation distance, thickness of the composition, etc. of the light source, but it is sufficient to irradiate for, for example, 0.01 hours or more, preferably 0.05 hours or more. EXAMPLES
[0098] The present embodiment will be described in more detail below with reference to examples, but the present embodiment is not limited to these examples.
[0099] (Evaluation method) [Plaster sensory test] The prepared urethane (meth)acrylate resin mortar composition was applied to a concrete plate with a trowel, and the trowel workability (stickiness and lightness to the trowel) and sagging were evaluated. The trowel workability was evaluated by the following criteria: stickiness and lightness to the trowel when the resin mortar composition was applied to a concrete plate placed on the floor surface with a thickness of about 0.5 cm. The sagging was evaluated by the following criteria: the degree of sagging due to the weight of the resin mortar composition when it was applied to a concrete plate placed vertically from the ground with a thickness of about 2 cm and left to stand.
[0100] "Sticky" Criteria: 1: When removing the trowel from the mortar, it feels sticky and puts strain on your arms. 2: When you remove the trowel from the mortar, it feels sticky, but it doesn't strain your arms. 3: The curling iron comes off easily, so there is no strain on your arms.
[0101] "Lightness of the trowel" Criteria: 1: It is heavy and puts strain on your arms. 2: The burden is light, but it requires force when applying. 3: It can be applied smoothly with almost no effort.
[0102] "Sagging" Criteria: 1: Dripping occurs when left to stand. 2: There is no dripping when left still, but dripping occurs when subjected to slight vibration. 3: No sagging occurs even when subjected to vibration.
[0103] [Wet surface adhesion test] Normal concrete slab (60 x 300 x 300) specified in JIS A 5371-2010 The surface to be used for the adhesion test was thoroughly cleaned of fragile and powdered materials and prepared by wiping with a soft, clean cloth. The concrete formwork for the adhesion test was set up according to JIS A 6909:2014, section 7.10, but because the size of the test specimen was different, a rubber plate with a width of 10 mm and a thickness of 10 mm was used as a substitute for the formwork, and the rubber plate was attached to a normal concrete plate with double-sided tape, etc., to create a test specimen for evaluating adhesion strength. This test specimen was submerged in water for 24 hours so that it was sufficiently hydrated. After that, 5 mm from the top side was exposed to the water surface, and a wet test was performed, according to the method described in Figure 8 of the test procedure after immersion in JIS A 6909:2014, section 7.10. Also, just before applying the adhesive, the concrete surface was wiped with a dry cloth until there was no floating water on it. The resin mortar composition was applied with a trowel or spatula to a thickness of about 10 mm, and cured for one day at 25°C and 50% humidity, after which an adhesion test was performed. The adhesion strength test was performed using a Kenken adhesion tester (Technotester Model R-10000ND), a tensile tester certified by the Architectural Finish Society of Japan, at five locations on each concrete plain slab specimen, and the average value of the five locations was calculated. In terms of adhesion to inorganic structures, an adhesion strength of 1.5 N / mm2 or more was evaluated as "good."
[0104] <Growth rate> The resin mortar composition for testing was prepared as a 1A type test piece in accordance with JIS K 7161-2:2014, 6.1 and 6.2, with the composition shown in Table 2. The tensile strength was measured in accordance with JIS K 7161-2:2014. The measurement was performed using an electromechanical universal material testing machine "5900R" (manufactured by Instron) at a test speed of 5 mm / min, and the value was obtained based on JIS K 7161-1:2014.
[0105] (raw materials) The raw materials used in the production of each urethane (meth)acrylate resin mortar composition in the examples and comparative examples are as follows.
[0106] [Urethane (meth)acrylate resin (A)] Urethane methacrylate resin (A-1): Urethane methacrylate resin Rigolac (registered trademark) KRN-880, Resonac Co., Ltd.
[0107] (Synthesis Example 1) "Synthesis of urethane (meth)acrylate resin (A-2)" In a four-neck flask equipped with a thermometer, a stirrer, a gas inlet, and a reflux condenser, 136 g of polypropylene glycol (weight average molecular weight 400), 170 g of 4,4'-diphenylmethane diisocyanate, 120 g of Light Ester 2EG (Kyoeisha Chemical Co., Ltd.), and 0.1 g of dibutylhydroxytoluene were charged and heated to 60°C in a dry air atmosphere. When the internal temperature reached 60°C, 0.004 g of dibutyltin dilaurate was added as a catalyst, and the temperature was raised to 70°C and stirred for 1 hour, after which the IR peak of the reaction product was measured. Wave number 2270 cm -1 and wave number 1730cm -1 When no change was observed in the peak ratio, 93 g of hydroxypropyl methacrylate was added over 30 minutes, followed by the addition of 0.02 g of dibutylhydroxytoluene, and the temperature was raised to 75°C to carry out the reaction. -1 The reaction was terminated when it was confirmed that the peak of was disappeared. 380 g of dicyclopentenyloxyethyl methacrylate (manufactured by Resonac Co., Ltd., FA-512MT) and 100 g of dicyclopentanyl methacrylate (manufactured by Resonac Co., Ltd., FA-513M) were added as radical polymerizable monomers to obtain 1000 g of urethane methacrylate resin (A-2).
[0108] [VE Resin (A')] (Synthesis Example 2) "Synthesis of vinyl ester resin (A'-1)" A 1L four-necked separable flask equipped with a stirrer, reflux condenser, gas inlet tube and thermometer was charged with 150.4g of AER-2603 (Asahi Kasei Corporation, bisphenol A type epoxy resin: epoxy equivalent 189), 188.4g of SR-16H (Sakamoto Yakuhin Kogyo Co., Ltd., 1,6-hexanediol diglycidyl ether), 0.255g of methyl hydroquinone, and 1.5g of DMP-30 (Tokyo Kasei Kogyo Co., Ltd., 2,4,6-tris(dimethylaminomethyl)phenol), and the temperature was raised to 110°C. After the temperature was raised to 110°C, 172g of methacrylic acid (Mitsubishi Rayon Co., Ltd.) was added dropwise over about 30 minutes, and the reaction was continued for about 4 hours. When the acid value reached 10mgKOH / g, the reaction was terminated, and a vinyl ester compound was obtained. Next, 256.3 g of dicyclopentenyloxyethyl methacrylate (manufactured by Hitachi Chemical Co., Ltd., FA-512MT) and 85.4 g of dicyclopentanyl methacrylate (manufactured by Hitachi Chemical Co., Ltd., FA-513M) were added as radically polymerizable unsaturated monomers to obtain a radically polymerizable compound (A'-1).
[0109] [Water reducing agent (B)] B1: Naphthalenesulfonic acid-formaldehyde condensate sodium salt, Mighty 100 (Kao Corporation) B2: Melanin formaldehyde condensate, Sikament FF-86 / 100 (Sika Japan Co., Ltd.) B3: Polycarboxylic acid-based water-reducing agent, Leobuild SP85V (NMB Corporation)
[0110] [Aggregate (C)] C2: Portland cement, UBE Mitsubishi early-strength Portland cement (UBE Mitsubishi Cement Corporation) C3: No. 6 silica sand, No. 6 silica sand (Mikawa Silica Co., Ltd.) C4: No. 8 silica sand, No. 8 silica sand (Mikawa Silica Co., Ltd.)
[0111] [Metal-containing compounds (D)] D1: 6%-Mn, manganese octoate (Toei Chemical Co., Ltd., manganese hexoate)
[0112] [Thiol compound (E)] E1: KarenzMT (registered trademark) BD1 (1,4-bis(3-mercaptobutyryloxy)butane, molecular weight 299.43), a bifunctional secondary thiol manufactured by Showa Denko KK, was used.
[0113] [Radical polymerization initiator (G)] G1: Cumene hydroperoxide (CHP), Percumyl (registered trademark) H-80 manufactured by NOF Corporation, was used as a thermal radical polymerization initiator. [Thixotropic agent (K1)] K1: Thixotropic agent (Aerosil), Aerosil-20 (Aerosil Japan Co., Ltd.)
[0114] Example 1 "Preparation of urethane (meth)acrylate resin mortar composition" (1) Process (S1): The urethane (meth)acrylate (A) was thoroughly mixed with the water reducing agent (B), aggregate (C), and other components, such as a thixotropic agent (K1), in the amounts shown in Table 1, to obtain a urethane (meth)acrylate resin mortar composition.
[0115] The mixing conditions in each step were as follows. Mixer: HOMOGENIZING DISPER Model 2.5 (Primix) Agitation speed: 3000-5000 rpm Temperature: 25℃
[0116] "Plaster sensory test" The trowelability of the resulting urethane (meth)acrylate resin mortar composition was evaluated by the above-mentioned evaluation method. The results are shown in Table 1.
[0117] (Examples 2 to 8, Comparative Examples 1 to 8) A urethane (meth)acrylate resin mortar composition was obtained in the same manner as in Example 1, except that the components and amounts of each component shown in Table 1 were used. A urethane (meth)acrylate resin mortar composition was also prepared in the same manner as in Example 1. Then, the trowel workability of each of the obtained resin mortar compositions was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0118] Example 9 (1) Process (S1): The urethane (meth)acrylate (A) was thoroughly mixed with the metal-containing compound (D) and the thiol compound (E) in the amounts shown in Table 2 to obtain a resin composition 1. (2) Process (S2): The resin composition 1 obtained in step 1 (S1) was thoroughly mixed with the radical polymerization initiator (G) in the blending amount shown in Table 2 to obtain a curable resin composition 2. (2) Process (S3): The curable resin composition No. 2 obtained in step 2 (S2) was thoroughly mixed with the water reducing agent (B), aggregate (C), and other components such as a thixotropic agent (K1) in the amounts shown in Table 2 to obtain a urethane (meth)acrylate resin mortar composition. (Examples 10 to 11, Comparative Examples 8 to 10) A urethane (meth)acrylate resin mortar composition was obtained in the same manner as in Example 1, except that the components and amounts thereof shown in Table 2 were used. A cured product of the urethane (meth)acrylate resin mortar composition was also produced in the same manner as in Example 1.
[0119] "Wet surface adhesion test" The cured product of the obtained urethane (meth)acrylate resin mortar composition was evaluated by the above-mentioned evaluation methods. The results are shown in Table 2.
[0120] "Growth rate" The cured product of the obtained urethane (meth)acrylate resin mortar composition was evaluated by the above-mentioned evaluation methods. The results are shown in Table 2.
[0121] [Table 1]
[0122] [Table 2]
[0123] The meanings of the symbols of each component in Tables 1 and 2 are as follows: UMA resin: urethane (meth)acrylate resin VE resin: Vinyl ester resin B1: Naphthalenesulfonic acid-formaldehyde condensate sodium salt, Mighty 100 (Kao Corporation) B2: Melanin formaldehyde condensate, Sikament FF-86 / 100 (Sika Japan Co., Ltd.) B3: Polycarboxylic acid-based water-reducing agent, Leobuild SP85V (NMB Corporation) C2: Portland cement, UBE Mitsubishi early-strength Portland cement (UBE Mitsubishi Cement Corporation) C3: No. 6 silica sand, No. 6 silica sand (Mikawa Silica Co., Ltd.) C4: No. 8 silica sand, No. 8 silica sand (Mikawa Silica Co., Ltd.) D1: 6%-Mn, manganese octoate (Toei Chemical Co., Ltd., manganese hexoate) E1: KarenzMT (registered trademark) BD1 (1,4-bis(3-mercaptobutyryloxy)butane, molecular weight 299.43), a bifunctional secondary thiol manufactured by Showa Denko KK, was used. G1: Cumene hydroperoxide (CHP), Percumyl (registered trademark) H-80 manufactured by NOF Corporation, was used as a thermal radical polymerization initiator. K1: Thixotropic agent (Aerosil), Aerosil-20 (Aerosil Japan Co., Ltd.)
[0124] As shown in Table 1, the urethane methacrylate resin mortar compositions containing the water reducing agent B of Examples 1 to 9 have three characteristics of stickiness, lightness of the trowel, and runnability at a high level in the plastering sensory evaluation. The sodium salt of naphthalenesulfonic acid-formaldehyde condensate and the melamine formaldehyde condensate have particularly good plastering sensory evaluations. In contrast, Comparative Examples 1 to 7, which do not contain the water reducing agent B, do not have the three characteristics in the plastering sensory evaluation. In particular, Comparative Examples 1, 3, and 7 improve runnability by containing a large amount of the thixotropic agent (K1), but the lightness of the trowel is deteriorated due to a trade-off relationship. In Comparative Examples 2 and 5, the ratio of the aggregate C to the resin composition is reduced to improve the lightness of the trowel, but the stickiness is deteriorated by increasing the ratio of the resin composition. Comparative Example 8 shows that the vinyl ester resin composition A' has no effect in the plastering sensory evaluation even if it contains the water reducing agent B. Table 2 shows the properties of the cured resin mortar composition. In Examples 9 to 11 and Comparative Example 8, by containing both the metal-containing compound D and the thiol compound E having a specific structure in the resin composition A, it is possible to ensure adhesion when applied to a wet structure, and when the cured product has a certain degree of elongation or more as in Examples 9 and 11, it can conform to the structure, and therefore has excellent durability after application.
Claims
1. A urethane (meth)acrylate resin (A); A water reducing agent (B); A urethane (meth)acrylate resin mortar composition comprising: an aggregate (C);
2. The urethane (meth)acrylate resin mortar composition according to claim 1, wherein the water-reducing agent (B) is at least one selected from the group consisting of naphthalenesulfonate-formaldehyde condensates, melanin-formaldehyde condensates, styrenesulfonic acid copolymers, polycarboxylic acids, ligninsulfonic acid, polystyrenesulfonic acid, naphthalenesulfonic acid, and melanin sulfonic acid water-reducing agents.
3. The urethane (meth)acrylate resin mortar composition according to claim 1 or 2, further comprising a metal-containing compound (D) and a thiol compound (E).
4. The urethane (meth)acrylate resin mortar composition according to claim 1 or 2, further comprising a radically polymerizable unsaturated monomer (M).
5. The urethane (meth)acrylate resin mortar composition according to claim 1, wherein the water reducing agent (B) is at least one water reducing agent selected from the group consisting of naphthalenesulfonate-formaldehyde condensates, melamine-formaldehyde condensates, and styrenesulfonic acid copolymers.
6. The urethane (meth)acrylate resin mortar composition according to claim 1 or 2, characterized in that the content of the aggregate (C) is 200 to 800 parts by mass per 100 parts by mass of the urethane (meth)acrylate resin (A).
7. The urethane (meth)acrylate resin mortar composition according to claim 1 or 2, further comprising a radical polymerization initiator (G).
8. The urethane (meth)acrylate resin mortar composition according to claim 1 or 2, characterized in that the urethane (meth)acrylate resin (A) has a number average molecular weight of 1,000 to 50,000.
9. A cured product of the urethane (meth)acrylate resin mortar composition according to claim 1 or 2.
Citation Information
Patent Citations
Low-shrinkage unsaturated polyester resin composition
JP1993222282A
Production of low-shrinkage unsaturated polyester resin composition
JP1999315198A
Low-shrinkage unsaturated polyester resin composition
JP2794802B2
Radically polymerizable resin composition and cured product of same
WO2021132140A1